NEBIVOLOL IN TREATMENT OF STABLE EXERTIONAL ANGINA PECTORIS - Y. V. Gavrilov; V. A. Sulimov; V. I. Makolkin (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate antianginal and antiischemic efficiency of nebivolol in patients with stable angina pectoris.Material and methods. 100 patients with ischemic heart disease showing stable exertional angina pectoris and having no contraindications to beta-blockers were studied. After 5-7 days of control period 50 randomly selected patients began to take nebivolol in initial dose of 5mg once daily and 50 patients started to take metoprolol in initial dose of 50 mg twice daily. Duration of treatment was 8 weeks. Efficiency of treatment was assessed according to the results of control treadmill assessment and control daily ECG monitoring.Results. 56-day therapy with nebivolol at a dose of 7,5 mg per day results in increase in duration of treadmill test before angina or ST depression (p<0.05). Antianginal and antiischemic effect of nebivolol 7.5 mg once daily is rather similar with that of metoprolol in average daily dose of 175 mg. Nebivolol compared to metoprolol significantly (p<0.05) more effectively reduces the number of silent myocardial ischemia.Conclusion. Nebivolol is an efficient antianginal and antiischemic drug for patients with stable exertional angina pectoris.